PENINGKATKAN KETERAMPILAN PIDATO DENGAN MODEL SIMULASI MAHASISWA SEMESTER GASAL PBSI UNSOED - Martha, Nila Ulfa (BAHASTRA, 2015)
This research aim to improve speech skill of PBSI Unsoed student in odd semester after applied simulation model. Research method is descriptive quantitative and descriptive qualitative. Desain research used class action. Process research of class action are cycle I and cycle II. Research result show an increase in speech skills of student. The average value an thoroughness learning has increased significantly. Cycle I 44,75 (20%) and cycle II 82,5 ( 92,5%). Observation result to student attitude is also show the existence of improvement become betterly. Students more enthusiastic about their lessons and learning becomes fun.